2015
DOI: 10.1590/1678-4499.0245
|View full text |Cite
|
Sign up to set email alerts
|

Surface energy exchange and evapotranspiration from cotton crop under full irrigation conditions in the Rio Grande do Norte State, Brazilian Semi-Arid

Abstract: The main objectives of this study were documenting how energy balance partitioning and ET vary seasonally along each growth season of cotton crop under full irrigation conditions in the Brazilian semiarid. The studied area was located in the Apodi Plateau, which is located on west of Rio Grande do Norte state and is an area with extensive agricultural suitability and semiarid climate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
3
9
0
2
Order By: Relevance
“…The increase lE/Rn from initial to middle season, in accordance with the increase of the LAI, is expected since in this period the muskmelon crop has high growth and development changing from seedlings (very low LAI) to middle season when it reaches the apex of its development during only about 50 days (Table 3). During middle season (from flowering to start of fruit maturity) the crop reaches the prime of their photosynthetic, physiological and metabolic activities and requires maximum water use (Bezerra et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase lE/Rn from initial to middle season, in accordance with the increase of the LAI, is expected since in this period the muskmelon crop has high growth and development changing from seedlings (very low LAI) to middle season when it reaches the apex of its development during only about 50 days (Table 3). During middle season (from flowering to start of fruit maturity) the crop reaches the prime of their photosynthetic, physiological and metabolic activities and requires maximum water use (Bezerra et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Th e partitioning of the available energy balance can be evaluated by analyzing the dimensionless evaporative fraction (Λ), defi ned as a ratio of latent heat fl ux to available energy fl ux, and it is usually used to characterize the energy partition over the land surface (Shen et al 2004;Bezerra et al 2015): where β is the Bowen ratio (Bowen 1926), calculated by following equation, only for daytime period with positive available energy (Rn -G > 0) (Perez et al 1999;Bezerra et al 2015). Th is equation is derived from empirical relationships between fl uxes and vertical gradients, assuming that turbulent diff usion coeffi cients for the transport of heat and water vapor are equal (Verma et al 1978;Perez et al 1999):…”
Section: Methodsmentioning
confidence: 99%
“…Bezerra et al, (2014) found that energy balance partitioning and ET varies seasonally along each growth stages of cotton. Ding et al, (2013) studied that over banana crop latent heat flux was the dominant among other component of energy balance.…”
Section: Issn: 2319-7706 Volume 6 Number 10 (2017) Pp 130-137mentioning
confidence: 96%
“…The largest value of LE/Rn observed in Cropland/Agroforestry land cover areas is expected because crop reaches higher foliar area providing full soil cover with much higher LAI than the other landcover classes. Within a class, the percentage of Rn converted into G(G/Rn) and H(H/Rn) varies inversely with LAI and LE/Rn [88]. Physically, this trend is always expected because LE and H fluxes are controlled by soil water availability [89].…”
Section: Partitioning Of the Net Radiation (Rn) To Le H And G Acrossmentioning
confidence: 99%